THE LAW HAS BEEN MUAMALAH THROUGH SOCIAL MEDIA (STUDY OF MUI FATWA ANALYSIS NUMBER 24 OF 2017) - Gunawan, Asep; Nur Amalina, Nadilah; Fidha, Rofiqotul; Ratna, Ratna; Putriani, Siti Nurmah; Hadi Harisuddin, Abdul (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The digital era is an era in which all human life can be carried out easily, one of which is in the process of communication and information dissemination. The widespread use of social media as a tool for disseminating information and communication has had many positive impacts. In addition to the positive impact, many also have a negative impact on its users. One of the impacts that is increasingly being felt these days is cyber bullying or bullying through cyberspace. Therefore, to find out how existing regulations in Indonesia view cyber bullying cases, this research is more specific and based on MUI Fatwa No. 24 of 2017. The method used in this research is a library study type. research. This type of research is carried out by observing various sources and literature related to the problem to be studied. The results of this study are in fatwa no. 24 of 2017, the Indonesian Ulema Council regulates the use of the internet for social media purposes. Instead, the contents of this fatwa emphasize the wise use of social media to avoid namimah, bullying, slander, slander, and hoaxes. However, the use of the internet by e-commerce for trading purposes is only one aspect of the overall picture. In fact, according to a 2016 survey, more people use the internet for e- commerce than they use social media. MUI's response to the needs of the community in dealing with muamalah in the online world is another important aspect.